Hydrological Resilience Using Water System Carrying Capacity Indicators in the Tiworo Watershed, Muna Island - Gandri, La; Sudia, La Baco; Agusrinal, Agusrinal; Teke, Junartin; Sakti, Abdul; Yunus, Lukman (JOURNAL OF SOILSCAPE AND AGRICULTURE, 2026)
The ecological integrity of many watersheds is declining due to land conversion, deforestation, and urbanization, which increase surface runoff, reduce infiltration, and trigger discharge instability. A quantitative evaluation that simultaneously links KRA, KAT, sediment load, flood frequency, and IPA parameters with water governance aspects to assess the degree of hydrological resilience in the archipelago. This study aims to assess hydrological resilience based on the carrying capacity of the water system in the Tiworo Watershed, Muna Island. The method used refers to the Minister of Forestry Regulation No. P.61/Menhut-II/2014 by measuring the variables of flow regime efficiency, annual flow coefficient, sediment load, flood intensity, and water use index. The results show that the carrying capacity of the Tiworo Watershed water system has a performance value of 96.25, which is categorized as moderate. This carrying capacity value can be interpreted as functionally having sufficient capacity, but is vulnerable to ecological and anthropogenic pressures.